Mental self and object representations of 7–10-year-old boys with behavior difficulties - Bieliauskaitė, R.; Kuraitė, E. (Psichologija, 2011)
This study looked into the links between the external difficulties and the internal “self” and objects representations. The aim of the study was to compare the internal representations of the children with the behavioral difficulties to children with no behavioral difficulties in order to gain a better understanding of the inner structures which could be linked to inappropriate and aggressive behavior. Boys with behavioral difficulties aged 7–10-year-old were recruited and compared with the boys of the same age with no behavioral difficulties. 20 boys from the clinical sample and 10 boys from the control group – 30 boys in total – were assessed. The measure used to assess external difficulties was Child Behavior Checklist. Projective tools such as Children Apperception Test and Kinetic Family Drawing were applied to assess the representations. The results of the projective methods were analyzed with the “Social Cognition and Object Relations Scale“ (SCORS) and “The Global Rating Scale”. According to SCORS four dimensions of internal representations were assessed: complexity of representations of people, affective quality of representations, emotional investment in relationships, values and moral standards and understanding social causality. The study results show that inner “self” and object representations of the boys with behavioral difficulties are different from the ones of the boys without behavioral difficulties. Representations of the clinical sample are less differentiated, have a negative emotional tone. These boys also show a lower capacity for emotional investment in relationships and moral standards, an impaired understanding of social causality. Boys with the behavioral difficulties see others as indifferent, rejecting, vulnerable, unreliable, inconsistent and not being able to help. Their inner “self” is represented as vulnerable and rejected, unattached to his family. The projective method used in the study and analysis of the data allows us to predict behavioral difficulties. Mental representations of children with behavioral difficulties have specific characteristics. The different experiences in long term psychotherapy could transform those characteristics into more adaptable ones.